Stone wood and metal in the memorial sculpture of Ukrainian historical cemeteries of the Polish-Ukrainian borderlands - Stasyuk, Olena (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2018)
The memorial sculpture of Ukrainian historical cemeteries of the Polish-Ukrainian borderlands was analyzed. The existing state of objects is characterized. Use and preservation of materials – stone wood and metal – from which the typical models of the memorial imagery are executed was investigated. Special attention is paid to the discovery and research of unique samples of the memorial plastics made of different materials which were discovered during field works.